TANGGUNG JAWAB NOTARIS TERHADAP CALON NOTARIS YANG SEDANG MAGANG DITEMPATNYA - Leptohoeve Tobias Tunjan; Suprapto; Saprudin (LPPM STIH Awang Long, 2023)
The purpose of this research is to analyze the responsibilities of the notary to the notary candidate who is doing an internship in their office. The type of this research is normative research, namely research by examining the applicable laws and regulations. The characteristic of the research conducted is prescriptive research, namely research that aims to get suggestions about what to do, to overcome certain problems. First Research Result : The legal relationship between an internship notary and the Notary is based on the statutory regulations contained in Article 16 Section (1) letter N of the Notary Act Number 2 of 2014 concerning Apprenticeship which says that in carrying out their position the Notary is obliged to accept the notary candidate apprentice. Furthermore: There are no legal consequences for the notary who does not fulfill their rights and obligations as an apprentice recipient of a prospective notary public because this is not further regulated in the notary act, but there are other sanctions, namely in the form of revocation of their status as a notary receiving apprenticeship and a certificate of apprenticeship that issued cannot be recognized by the association based on the decision of the relevant INI Regional Management Meeting. Second : There are no legal consequences for the notary who does not fulfill their rights and obligations as an apprentice recipient of a prospective notary public because this is not further regulated in the notary act, but there are other sanctions, namely in the form of revocation of their status as the notary receiving apprenticeship and a certificate of apprenticeship that issued cannot be recognized by the association based on the decision of the relevant INI Regional Management Meeting.